Salient beliefs related to secondary distribution of COVID-19 self-test kits within social networks - Bien-Gund, Cedric H.; Sarbaugh, Molly; Perrine, Lily; Dugosh, Karen; Gross, Robert; Fishman, Jessica (Frontiers in Public Health, 2024)
Background Widespread access to testing is critical to public health efforts to control the COVID-19 pandemic. Secondary distribution of COVID-19 self-test kits, where an individual distributes test kits to others in their social networks, is a potential strategy to improve access to testing. In this qualitative study, we identified salient beliefs about distributing and accepting COVID-19 self-test kits within one’s social network, as well as ordering COVID-19 self-test kits from the government. Methods We recruited 61 participants from a randomized controlled trial (NCT04797858) in Philadelphia, Pennsylvania to elicit beliefs about (1) distributing COVID-19 self-test kits within one’s social network, (2) receiving test kits from social contacts, and (3) ordering self-test kits from the government. Using validated, open-ended question stems, we identified the most common set of beliefs underlying attitudes, perceived norms (or social referents), and perceived behavioral control (or self-efficacy) toward each of these behaviors. Results Twenty-seven out of 30 (90%) of participants who received self-test kits reported distributing the kits to social contacts. These participants described altruistic beliefs about giving others access to testing, and felt approval from family members, friends, and others in their social networks. When receiving test kits from social network contacts, participants described advantages of test kit convenience, but some voiced concern about test kit tampering and confusing instructions. Participants also described perceived logistic barriers to distributing and receiving self-test kits, such as delivering or transporting test kits, or finding time to meet. Participants who ordered test kits from the government also described increased convenience of test access, but described different logistic barriers such as delays in test kit delivery, or not receiving test kits at all. Conclusion In comparison with government-ordered test kits, the secondary distribution of COVID-19 self-test kits raised unique concerns about test kit quality and instructions, as well as distinctive logistic barriers related to distributing self-test kits to network contacts, which were not raised for test kits ordered from the government. This study demonstrates that beliefs may vary depending on the type of testing behavior, and behavioral interventions may benefit from developing messages tailored to specific testing strategies.